PEMETAAN LAHAN PERTANIAN DI KABUPATEN LOMBOK TIMUR MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) - Ansar ANSAR; Murad Murad; Guyup Mahadhian Dwi Putra; Hanifa Hartuti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2020)
This study aimed to analyze and to map the ability of agricultural land in East Lombok Regency West Nusa Tenggara Province using Geographic Information System (GIS). The method used in this research is descriptive to analyze and match data on the condition of the study area with the criteria for land capability class refer to the Minister of Environment Regulation No.17 of 2009. The parameters observed were soil texture, slope, drainage, effective depth, erosion, and flood threat. The results showed that East Lombok Regency was included in 6th land capability classes, namely class II, III, IV, VI, VII and VIII. Land with class IV dominates the research area is 501.04 km2 which is spread almost in all districts in East Lombok Regency. Areas with class II, III, and IV land are the land that can be used for agricultural cultivation, while class VI, VII, and VIII land is the land with heavy inhibitor factors, so it is better left in natural conditions.